2009
DOI: 10.1002/cbic.200900323
|View full text |Cite
|
Sign up to set email alerts
|

Of Two Make One: The Biosynthesis of Phenazines

Abstract: Five easy steps: Phenazines are redox‐active bacterial secondary metabolites that possess broad‐specificity antibiotic activity and can also play an important role as virulence factors in infectious disease. Their biosynthesis from two molecules of chorismic acid is catalyzed by enzymes encoded in the conserved phz operon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
133
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 80 publications
0
133
0
3
Order By: Relevance
“…Previous studies demonstrated that Pseudomonas species utilize combinations of conserved regulatory systems including two-component signal transduction (TCST), quorum sensing (QS), post-transcriptional control by small non-coding RNAs and other regulators that are integrated into sensory networks to control phenazine production in response to diverse environmental inputs (Mavrodi et al, 2006;Mentel et al, 2009;Gross & Loper, 2009). In P. chlororaphis, as in most other phenazineproducing bacteria, synthesis of the core phenazine PCA is encoded by a conserved set of biosynthetic genes (Pierson et al, 1995;Mavrodi et al, 2006;Mentel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that Pseudomonas species utilize combinations of conserved regulatory systems including two-component signal transduction (TCST), quorum sensing (QS), post-transcriptional control by small non-coding RNAs and other regulators that are integrated into sensory networks to control phenazine production in response to diverse environmental inputs (Mavrodi et al, 2006;Mentel et al, 2009;Gross & Loper, 2009). In P. chlororaphis, as in most other phenazineproducing bacteria, synthesis of the core phenazine PCA is encoded by a conserved set of biosynthetic genes (Pierson et al, 1995;Mavrodi et al, 2006;Mentel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In P. chlororaphis, as in most other phenazineproducing bacteria, synthesis of the core phenazine PCA is encoded by a conserved set of biosynthetic genes (Pierson et al, 1995;Mavrodi et al, 2006;Mentel et al, 2009). Additionally, one or more accessory genes encode terminal modifying enzymes responsible for the conversion of the core phenazine PCA into other derivatives (Mavrodi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several biosynthetic studies have demonstrated that phenazine-1,6-dicarboxylic acid is a universal precursor for may phenazine secondary metabolites. 16,17 The HMBC spectrum also showed correlations of the methyl signal (d Thus, the structure of compound 5 was determined as shown in Figure 1, which we have named yorophenazine. From the literature, SB 212305 is the only phenazine antibiotic linked to N-acetylcysteine.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…Because phenazine production has such an extensive influence on bacterial fitness and microbe-host interactions, the regulation of phenazine production has received much attention [2,11,12]. As in other Pseudomonas species, phenazine biosynthesis in P. chlororaphis 30-84 is regulated by the PhzR/PhzI quorum sensing (QS) system, which is located directly upstream of the phenazine biosynthetic operon (annotated as phzXYFABCD in P. chlororaphis 30-84) [2,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…As in other Pseudomonas species, phenazine biosynthesis in P. chlororaphis 30-84 is regulated by the PhzR/PhzI quorum sensing (QS) system, which is located directly upstream of the phenazine biosynthetic operon (annotated as phzXYFABCD in P. chlororaphis 30-84) [2,12,13]. PhzI, a LuxI homologue, encodes an AHL synthase that produces N-acyl-homoserine lactone (AHL) signals [14].…”
Section: Introductionmentioning
confidence: 99%